A new look at the comparative physiology of insect and human hearts - Sláma, Karel (Journal of insect physiology, 2012)
Recent electrocardiographic (ECG) studies of insect hearts revealed the presence of human-like, involuntary and purely myogenic hearts. Certain insects, like a small light-weight species of hoverfly (Episyrphus balteatus), have evolved a very efficient cardiac system comprised of a compact heart ventricle and a narrow tube of aorta, which evolved as an adaptation to sustained hovering flights. Application of thermocardiographic and optocardiographic ECG methods revealed that adult flies of this species use the compact muscular heart chamber (heart ventricle) for intensive pumping of insect "blood" (haemolymph) into the head and thorax which is ringed all over with indirect flight musculature. The recordings of these hearts revealed extremely high, record rates of forward-directed, anterograde heartbeat (up to 10Hz), associated with extremely enhanced synchronic (not peristaltic) propagation of systolic myocardial contractions (32.2mm/s at room temperature). The relatively slow, backward-directed or retrograde cardiac contractions occurred only sporadically in the form of individual or twinned pulses replacing occasionally the resting periods. The compact heart ventricle contained bi-directional lateral apertures, whose opening and closure diverted the intracardiac anterograde "blood" streams between the abdominal haemocoelic cavity and the aortan artery, respectively. The visceral organs of this flying machine (crop, midgut) exhibited myogenic, extracardiac peristaltic pulsations similar to heartbeat, including the periodically reversed forward and backward direction of the peristaltic waves. The tubular crop contracted with a periodicity of 1Hz, both forwards and backwards, with propagation of the peristaltic waves at 4.4mm/s. The air-inflated and blindly ended midgut contracted at 0.2Hz, with a 0.9mm/s propagation of the peristaltic contraction waves. The neurogenic system of extracardiac haemocoelic pulsations, widely engaged in the regulation of circulatory and respiratory functions in other insect species, has been replaced here by a more economic, myogenic pulsation of the visceral organs as a light-weight evolutionary adaptation to prolonged hovering flight. Striking structural, functional and even genetic similarities found between the hearts of Episyrphus, Drosophila and human hearts, have been practically utilised for inexpensive testing of new cardioactive or cardioinhibitory drugs on insect heart.
Keywords: hemolymfa; Animals; Heart; Female; ženské pohlaví; srovnávací fyziologie; Myocardial Contraction; srdce; lidé; Hemolymph; Electrocardiography; elektrokardiografie; srdeční frekvence; Male; Diptera; kontrakce myokardu; zvířata; mužské pohlaví; Heart Rate; Physiology, Comparative; Humans